Prevalence and correlates of HIV risk among adolescents and young adults reporting drug use: Data from an urban Emergency Department in the U.S - Bonar, Erin E. (2014)
Adolescents and young adults who use substances are at particularly high risk for contracting Human Immunodeficiency Virus (HIV). The Emergency Department (ED) is a critical location for HIV prevention for at-risk youth. To inform future interventions in the ED, this study identifies correlates of HIV risk behaviors among substance using youth seeking ED care. Among 600 14-24-year-olds with past 6-month drug use, bivariate correlates of HIV risk included: older age, female gender, depressive symptoms, alcohol use, marijuana use, other drug use, and dating, peer, and community violence. Regression analyses indicated that older age, marijuana use, and dating violence were positively related to HIV risk. Results suggest HIV prevention efforts for youth in the urban ED should address marijuana use and dating violence as well as sexual risk behaviors.